Exposure to surrounding greenness and natural-cause and cause-specific mortality in the ELAPSE pooled cohort. (August 2022) - Bereziartua, Ainhoa; Chen, Jie; de Hoogh, Kees; Rodopoulou, Sophia; Andersen, Zorana J.; Bellander, Tom; Brandt, Jørgen; Fecht, Daniela; Forastiere, Francesco; Gulliver, John; Hertel, Ole; Hoffmann, Barbara; et al.
Graphical abstract: Highlights: Surrounding greenness exposure is inversely associated with natural-cause mortality. The association remained after adjusting for air pollution and traffic noise. Inverse association was observed for cause-specific mortality with less certainty. Abstract: Background: The majority of studies have shown higher greenness exposure associated with reduced mortality risks, but few controlled for spatially correlated air pollution and traffic noise exposures. We aim to address this research gap in the ELAPSE pooled cohort. Methods: Mean Normalized Difference Vegetation Index (NDVI) in a 300-m grid cell and 1-km radius were assigned to participants' baseline home addresses as a measure of surrounding greenness exposure. We used Cox proportional hazards models to estimate the association of NDVI exposure with natural-cause and cause-specific mortality, adjusting for a number of potential confounders including socioeconomic status and lifestyle factors at individual and area-levels. We further assessed the associations between greenness exposure and mortality after adjusting for fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ) and road traffic noise. Results: The pooled study population comprised 327, 388 individuals who experienced 47, 179 natural-cause deaths during 6, 374, 370 person-years of follow-up. The mean NDVI in the pooled cohort was 0.33 (SD 0.1) and 0.34 (SD 0.1) in the 300-m grid and 1-km buffer. In the main fully adjusted model, 0.1 unit increment of NDVI inside 300-m grid was associated with 5% lower risk of natural-cause mortality (Hazard Ratio (HR) 0.95 (95% CI: 0.94, 0.96)). The associations attenuated after adjustment for air pollution [HR (95% CI): 0.97 (0.96, 0.98) adjusted for PM2.5 ; 0.98 (0.96, 0.99) adjusted for NO2 ]. Additional adjustment for traffic noise hardly affected the associations. Consistent results were observed for NDVI within 1-km buffer. After adjustment for air pollution, NDVI was inversely associated with diabetes, respiratory and lung cancer mortality, yet with wider 95% confidence intervals. No association with cardiovascular mortality was found. Conclusions: We found a significant inverse association between surrounding greenness and natural-cause mortality, which remained after adjusting for spatially correlated air pollution and traffic noise.